Austria : Publication of Financial Sector Assessment Program Documentation-Technical Note on Financial Stability Analysis, Stress Testing, and Interconnectedness. (IMF Staff Country Reports; Country Report ;, 2020)
This technical note on Austria presents the Financial Stability analysis, stress testing, and interconnectedness. Austria's banking sector presents unique structural vulnerabilities. Private credit growth has supported the cyclical boom without jeopardizing household and corporate indebtedness. Profits of Austrian subsidiaries in Central, Eastern, and South-eastern Europe have increased recently; however, the cycle is turning and the ability of the sector to maintain a solid net interest margin may be further challenged. The Austrian authorities have targeted vulnerabilities related to interconnectedness by imposing Other Systemically Important Institution buffers also at the unconsolidated level. Institutional cooperation arrangements are shown to act as a shock absorber for idiosyncratic shocks, but holdings among participating members of respective IPSs may lead to substantial inward stability risks in a systemic event. Under favorable economic conditions inverse ownership contributes strongly to their capital generation by allowing partial redistribution of profits higher tier banks in the Raiffeisen sector earn on their more profitable international business.